Fluoride and sodium trimetaphosphate (TMP) release from fluoride varnishes supplemented with TMP - Michele Mauricio MANARELLI; Alberto Carlos Botazzo DELBEM; Célio PERCINOTO; Juliano Pelim PESSAN (Sociedade Brasileira de Pesquisa Odontológica, 2016)
Abstract This study assessed fluoride (F) and sodium trimetaphosphate (TMP) release into artificial saliva from varnishes containing 0%, 2.5%, and 5% NaF, supplemented or not with 5% TMP. The varnishes were applied on polyester sheets (n = 8/group), and F and TMP released into artificial saliva were measured for up to 24 hours. The amount of F and TMP released were directly related to NaF and TMP concentrations in the varnishes. The highest F release was seen for 5% NaF and 5% NaF + 5% TMP, whereas 5% TMP released the highest amount of TMP. However, the simultaneous addition of NaF and TMP to varnishes significantly reduced the amount of F and TMP released from the products.